2021
DOI: 10.1182/blood.2021011557
|View full text |Cite
|
Sign up to set email alerts
|

The age of the bone marrow microenvironment influences B-cell acute lymphoblastic leukemia progression via CXCR5-CXCL13

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) occurs most commonly in children, while chronic myeloid leukemia (CML) is more frequent in adults. The myeloid bias of hematopoiesis in elderly individuals has been considered causative, but the age of the bone marrow (BM) microenvironment (BMM) may be contributory. Using various murine models of B-ALL in young versus old mice, we recapitulated B-ALL preponderance in children versus adults. We showed differential effects of young versus old BM macrophages on B-ALL ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…CD8 + and CD4 + T cells, cancer-associated fibroblasts, cancer cells, and dendritic cells are able to secrete CXCL13, and CD8 + and CD4 + T cells, B cells, and cancer cells express CXCR5 ( Figure 2 ). Increasing research has reported the detection of CXCL13 in the tumor microenvironment of many different types of cancer [ 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. When the cancer microenvironment is enriched in CXCL13, the recruitment of CXCR5-expressing leukocytes to the tumor microenvironment increases.…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
“…CD8 + and CD4 + T cells, cancer-associated fibroblasts, cancer cells, and dendritic cells are able to secrete CXCL13, and CD8 + and CD4 + T cells, B cells, and cancer cells express CXCR5 ( Figure 2 ). Increasing research has reported the detection of CXCL13 in the tumor microenvironment of many different types of cancer [ 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. When the cancer microenvironment is enriched in CXCL13, the recruitment of CXCR5-expressing leukocytes to the tumor microenvironment increases.…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
“…Specifically, it is a matter of discussion regarding how representative mouse models of hematopoietic aging or leukemia development are and if further modeling should be conducted in aged mice instead of young animals to understand the context dependency of genetic and pharmacological perturbations. This is particularly relevant when discussing murine models for pediatric leukemias, where differential effects of young vs. old mice's BM microenvironment on B-ALL cells can be observed [213]. Concerns about animal welfare, costs, validity and applicability of outcomes when animal models are used must also be taken into consideration; however, applying the most recent biotechnology and technical advances, such as single-cell and high-throughput platforms, will allow for better exploitation of the biological resources.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages in young mice were found to produce higher levels of CXCL13 than those in old mice, and the CXCR5-CXCL13 axis promoted the proliferation of B-ALL cells in a young bone marrow microenvironment. Consistently, Cxcr5 deletion in B-ALL stem cells showed survival advantages in a B-ALL murine model, while high expression of CXCR5 in pediatric B-ALL predicted central nervous system relapse [ 97 ]. These data support the idea that the aging of bone marrow macrophages influences leukemia phenotype and highlight the CXCL13-CXCR5 axis as a potential target for B-ALL therapy.…”
Section: Targeting the Bone Marrow Microenvironment For CML Lscsmentioning
confidence: 94%
“…CML is rare in childhood but more prevalent among adults, due at least in part to increasing myeloid-biased hematopoiesis with age. Dr. Krause’s group explored the contributions of the aged microenvironment to CML pathogenesis [ 97 ]. C-X-C motif chemokine 13 (CXCL13) is a B cell chemo-attractant secreted by macrophages and is bound by its receptor CXCR5.…”
Section: Targeting the Bone Marrow Microenvironment For CML Lscsmentioning
confidence: 99%